2023
DOI: 10.1080/2162402x.2022.2161167
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and predictive value of Immunoscore and its correlation with ctDNA in stage II colorectal cancer

Abstract: This study aimed to validate the prognostic value of Immunoscore (IS) in stage II colorectal cancer (CRC), and explore the roles of IS and circulating tumor DNA (ctDNA) in the adjuvant treatment for early-stage CRC. Resected tumor samples from stage II CRC patients were collected from the Sun Yat-sen University Cancer Center. The densities of CD3+ and CD8+ lymphocytes were quantified and converted to IS and classified into Low, Intermediate (Int), and High groups according to predefined cutoffs. A total of 113… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 38 publications
(40 reference statements)
0
14
0
Order By: Relevance
“…To investigate this, we examined the roles of IS and ctDNA in guiding adjuvant treatment in Chinese early-stage colorectal cancer (CRC). 50 Our recent study demonstrated that IS-High patients, including clinically high-risk individuals, exhibited excellent clinical outcomes with no recurrences observed over a three-year follow-up period. Additionally, the 3-year DFS rates were 100% for IS-High, 76% for IS-Intermediate (IS-Int), and 47% for IS-Low ( p < 0.001).…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…To investigate this, we examined the roles of IS and ctDNA in guiding adjuvant treatment in Chinese early-stage colorectal cancer (CRC). 50 Our recent study demonstrated that IS-High patients, including clinically high-risk individuals, exhibited excellent clinical outcomes with no recurrences observed over a three-year follow-up period. Additionally, the 3-year DFS rates were 100% for IS-High, 76% for IS-Intermediate (IS-Int), and 47% for IS-Low ( p < 0.001).…”
Section: Introductionmentioning
confidence: 89%
“…While post-operative ctDNA assay effectively identified patients at heightened risk of recurrence, it was IS that reliably determined patients at low risk of recurrence. 50 This underscores the complementary roles of ctDNA and IS assessment in guiding treatment decisions and prognostication in early-stage CRC.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations